The Size and Economic Burden of External Debt in Syria - عيسى هيثم (Latakia University Journal - Economic and Legal Sciences Series, 2021)
There is a vast literature on external debt, but somehow it is a neglected topic in Syria both in academic and policy making discussions. This study focuses in the first (theoretical) part on reviewing the concept, main reasons, indicators, and solutions of external debt. In the secondpart, the study shows the development of external debt in Syria and its main economic burdens and comparison of external debt data in Syria with three categories of countries that are low income, developing, and Middle East and North Africa countries. The study found that Syria favors long-term borrowing mainly from bilateral sources. The level of external debt declined in Syria throughout the period of study. The ratio of external debt to GDP increased after 2011 but remained below than that in the categories of low income and developing countries. The ratio of external debt to exports was low in Syria prior to the crisisperiod but increased dramatically since its beginning.